The Implementation of Lesson Study in Students Field Experience Program at Primary School - Siti Halidjah (Universitas Tanjungpura, 2020)
The main focus of the implementation of lesson study was student activity in the classroom, assuming that the student's activities are related to the activities of the teacher while teaching in grade. Lesson study is a way to improve the quality of education that never ends. This study aimed to describe the application of lesson study in the implementation of practical experience programs for students in primary schools. This research used a qualitative approach. The source of data in this study was the students field experience program by applying the lesson study. The data were obtained from PGSD (primary teacher education) in FKIP (Faculty of Teacher Training and Education) students in the 7th semester. The research procedures used the stages of planning, implementation, data analysis, and report writing. Data collection techniques were direct observation techniques with data collection tools in the form of observation sheets. The results showed that the ability of students to compile learning plans increased 86.68 with the excellent category.